Authentic Materials And Task Design: A Teaching Amalgam - Aleyda Jasmin Alfonso Vargas; Paola Ximena Romero Molina (Colombian Applied Linguistics Journal)
The use of authentic materials in foreign language teaching has been a growing practice over the last few decades. With the emergence of technology, these materials are more accessible, particularly in digital formats. Despite being primarily designed for non-pedagogical uses, these materials have become valuable resources for English language learning. However, using them effectively for teaching and learning purposes requires a systematic structure. This article examines the use of authentic materials in relation to various language skills, with a particular focus on listening comprehension framed within a pre-, while-, and post-stage cycle at both local and international levels, with the latter referring to the Colombian context. A review of scholarship shows that the use of authentic materials is a seemingly frequent practice among teacher-researchers, but not among a larger audience of practitioners. Additionally, studies do not provide guidance on how to prepare practitioners to design appropriate activities that complement authentic materials. Therefore, after examining studies and based on our teaching-research experience, we aim to contribute to the implementation of a pedagogical strategy that combines the systematic use of authentic materials with listening comprehension and a task design that provides a balance of challenge and support.